Investigation and Synthesis of Some Novel Spiro Heterocycles Related to Indoline Moiety (Journal of Scientific Research, 2014)
Reactions of indole-2,3-dione 1 with 2-mercaptobenzimidazole, o-phenylenediamine, 2-aminophenol, 2-aminobenzothiazole, 2-aminobenzimidazole and 3-methyl-1-phenyl-2-pyrazolin-5-one were carried out to give compounds spiroindolethiazetobenzimidazole 2, spirobenzimidazole(oxazole)indoline 3a,b, benzothiazol(imidazol) iminoindolinone 4a,b and methyloxoindolylidenepyrazolone 5 respectively. Compound 5 was reacted with 2-aminophenol as well as o-phenylenediamine to give new spirooxazepine and diazepine derivatives 6a,b respectively. Reaction of 5 with nitrogen nucleophiles as well as carbon nucleophiles was investigated to furnish new spiro heterocycles 7-11. The reaction of 2-(2-oxo-1,2-dihydroindol-3-ylidene)malononitrile compound 12 with 3-methyl-1-phenyl-2-pyrazoline-5-one was carried out to give spiroindolopyranopyrazolo derivative 13. Compounds 4a,b was reacted with thioglycolic acid to give thiazolidinone derivatives 14a,b. Epoxidation of 5 using monoperoxyphthalic acid magnesium salt hexahydrate and hydrogen peroxide were executed to afford the novel dispiro (2-pyrazolin oxiraneindoline)dione compound 15. The chemical structures of the synthesized compounds were well established by elemental and spectral analyses.   Keywords: Spiroheterocycles; Epoxidation; Diazapines, Oxazepines; Spirothiazolidinone.  © 2014 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved.   doi: http://dx.doi.org/10.3329/jsr.v6i2.17590 J. Sci. Res. 6 (2), 303-317 (2014)